2005
DOI: 10.1086/497389
|View full text |Cite
|
Sign up to set email alerts
|

Accretion by the Secondary in η Carinae During the Spectroscopic Event. I. Flow Parameters

Abstract: We examine the influence of the gravity of the companion (the secondary) to the massive primary star Carinae on the winds blown by the primary and the secondary. The two winds collide with each other after passing through two respective shock waves, and escape the system while strongly emitting in the X-ray band. While during most of the 5.5 yr orbital period the companion's gravity has a negligible effect on the winds, we find that near periastron the companion's gravity may significantly influence the flow, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 40 publications
(126 citation statements)
references
References 38 publications
(103 reference statements)
5
120
1
Order By: Relevance
“…Soker et al have discussed in a series of papers an accretion model for η Car, which argues for the opposite effect that we just stated (see, e.g., Soker 2005, Kashi & Soker 2008a2009b). In their scenario, the companion accretes mass from η Car during periastron.…”
Section: Possible Scenarios For the Observed Changes In η Carmentioning
confidence: 55%
“…Soker et al have discussed in a series of papers an accretion model for η Car, which argues for the opposite effect that we just stated (see, e.g., Soker 2005, Kashi & Soker 2008a2009b). In their scenario, the companion accretes mass from η Car during periastron.…”
Section: Possible Scenarios For the Observed Changes In η Carmentioning
confidence: 55%
“…1948−2009, the wind-wind shocks were disrupted near each periastron passage. That allowed temporary accretion onto the secondary star (Soker 2003(Soker , 2005Soker & Behar 2006). Less far-UV radiation during each event resulted in the highexcitation lines to become temporarily weaker.…”
Section: Resultsmentioning
confidence: 99%
“…Davidson (2002) suggested that strong instabilities near periastron might cause the shocked gas to radiatively cool, reducing the emission at high energies. Soker (2005) and Akashi et al (2006) suggested that Bondi-Hoyle accretion of the primary star's wind by the companion star near periastron could suppress the companion's wind and thus reduce the emission from the colliding wind shock for a brief period. In optical observations, the He ii k4687 emission line, which is believed to arise near the WWC shock, decreased in concert with the X-ray drop (Steiner & Damineli 2004).…”
Section: The Absorber Around the Wwc Plasmamentioning
confidence: 99%